The nucleus Koelliker-Fuse (K-F) and parabrachial nuclear complex (PBNC) in man. Location, cytoarchitectonics and terminology in embryonic and adult periods, and comparison with other mammals - Petrovický, P (Journal fur Hirnforschung, 1989)
Series of sections from the brain stems of human embryos and adult individuals were studied for the topography and cytoarchitectonics of two different nuclei, both of them referred to in literature as the nucleus Koelliker-Fuse (nucleus K-F). A study of embryonic and comparative materials showed that the original descriptions by Koelliker (1896) and Fuse (1913) were identical with the pars compacta nuclei pedunculo-pontini in present-day nomenclature while the nucleus currently designated with their names was rather related to the principal nucleus of the trigeminus. For that reason, we recommend making a distinction between ncl. K-F (1896, 1913) and ncl. K-F (of recent authors); the former can be used mainly for embryonic material, the latter for comparative studies. However, the ncl. K-F (of recent authors) is not developed in adult humans. Descriptions are also included of the organization of the parabrachial nuclear complex and other structures of the isthmus mesencephali in the human embryo, and both are compared with the situation in adults humans.
Keywords: dospělí; plod; lidé; Fetus; Reticular Formation; Adult; retikulární formace; Humans